Implementation of Global Education in the Elementary School Curriculum to Improve Students' Intercultural Competence and Global Awareness - Mazidah, Ismi; Yustitia, Via (Jurnal Elementaria Edukasia, 2024)
The low levels of critical thinking and academic achievement among elementary students highlight the need for student‑centered instructional innovation. The Problem‑Based Learning (PBL) model is considered a promising response because it emphasizes authentic problem solving and encourages analytical and collaborative thinking. This study analyzes the effectiveness of PBL in improving elementary students’ learning outcomes and critical thinking skills. A quantitative approach was employed using a quasi‑experimental posttest‑only control group design. The participants were 55 fifth‑grade students at SDN Tambaksawah: 30 in the experimental class taught with PBL and 25 in the control class taught with conventional methods. Data were analyzed using the Independent Samples t‑Test at a 0.05 significance level. Results show a significant difference between groups, with Sig. (2‑tailed) = 0.001 < 0.05. The experimental class achieved a mean score of 79.53, while the control class averaged 68.68; Cohen’s d was 0.96 (large effect). These findings demonstrate that PBL effectively improves learning outcomes and critical thinking skills in elementary IPAS (Natural and Social Sciences) instruction.